Comparative Evaluation of Pain During Local Anaesthetic Administration with Conventional and Custom Modified Syringe in Pediatric Dental Patient: A Clinical Trail (Academia Journal of Medicine, 2025)
Aim: This clinical trial aimed to evaluate and compare the pain experienced during local anaesthetic administration using a conventional syringe versus a custom modified syringe designed with attractive emojis. The hypothesis was that the custom syringe would decrease anxiety and perceived pain.Materials and Methods: Thirty pediatric dental patients of age 6-8 years were randomly assigned to receive local anaesthesia with either a conventional disposable syringe or a custom modified syringe, decorated with vibrant, engaging emoji stickers. Pain levels were assessed immediately after the injection using the Wong-Baker FACES Pain Rating Scale, allowing patients to express their pain intensity through visual representation. Data were collected and analyzed to compare pain scores between the two groups.Results: The findings indicated that patients using the custom modified syringe reported significantly lower pain scores than those using the conventional syringe. The visual appeal of the custom syringe appeared to reduce anxiety, contributing to a more positive experience during the procedure.Conclusion: The incorporation of attractive emojis on syringes may serve as an effective strategy to reduce pain and anxiety associated with local anaesthetic administration. These findings suggest potential benefits for enhancing patient comfort and compliance in clinical settings. Further research is warranted to explore the long-term impact of such modifications on patient experiences in various medical procedures.
Keywords: Pain; Local Anesthesia; Wong-Baker FACES Pain Rating Scale